Arabic as a Catalyst of Political Consciousness: Tracing the Influence of the Arabic Language on Yoruba Political Activism - Busari Kehinde Kamorudeen; Folorunsho Mikail Adebisi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The article examines the Arabic language, mapping its impacts on Yoruba political activism with special reference to the Arabic-speaking Yoruba Muslims and their roles in the past and contemporary political activism of the Yoruba. The strategic capacity of using Arabic in the Yoruba political discourse has been unutilized despite its prominence in the political discourse of the Yoruba people. This study, using a qualitative approach, will use a historical analysis intermarried with case studies of the current situation. It is through archival materials that knowledge was to be gained about early Arabic influence on Yoruba political thinking and through mailing and web analysis of some speeches, social media posts, and publishing in Arabic, that contemporary political thought has been influenced by this conversational Arabic. The results indicate that Arabic has historically served as the vehicle in political learning and leadership among the Yoruba Muslim communities, thus developing a unique political identity. Literacy in the Arabic language enabled an interaction with greater Islamic ideologies and international political systems. In the present day, the knowledge of Arabic stimulates interaction at the linguistic level both in local and international contexts, contributes to the spread of political ideas, and promotes unity between Yoruba Muslims. The paper concludes that Arabic plays an important role in developing identity, political communication, and community activations. Subsequent studies must also explore the impact of Arabic on certain political movements in Yoruba. Policymakers and educators are advised to include Arabic political discourse in the curriculum to improve the level of civic activities among Yoruba Muslims.